Embolization as adjunctive treatment to achieve complete cure of ruptured arachnoid cyst associated with chronic subdural hematoma. (2nd January 2023) - Marnat, Gaultier; Jecko, Vincent; Gariel, Florent; Gimbert, Edouard; Liguoro, Dominique; Tourdias, Thomas
Abstract: Introduction: Chronic Subdural Hematoma (CSDH) is a rare but classical evolutive complication of arachnoid cysts (AC). Its management has rarely been evaluated to date. Several approaches have been proposed including conservative and surgical treatments. Endovascular treatment in such CSDH subtype remains poorly reported. Case presentation: We present here an original case of a 16 years-old-boy suffering from ruptured AC responsible for CSDH successfully treated with embolization. Conclusion: Endovascular approach may be considered in the treatment of CSDH related to arachnoid cyst rupture.